2000
DOI: 10.1243/1350650001543034
|View full text |Cite
|
Sign up to set email alerts
|

Recent thermohydrodynamic analyses and designs of thick-film bearings

M Tanaka

Abstract: This paper is a state-of-the-art report on recent thermohydrodynamic analyses and designs of journal and thrust bearings. Recent papers published in journals and proceedings on tribology mostly in the 1990s are referred to. Bearings not only for turbomachinery but also for automotive engines are covered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 52 publications
0
20
0
1
Order By: Relevance
“…Hydrodynamic slider bearings are widely used in industries for supporting the axial loads in machineries. Theoretical studies of hydrodynamic lubrication in slider bearings have been carried out by many investigators 1,2) in the past due to ease in its mathematical modeling. In some early works only Reynolds equation was solved in order to compute the bearing performance parameters.…”
Section: Overviewmentioning
confidence: 99%
“…Hydrodynamic slider bearings are widely used in industries for supporting the axial loads in machineries. Theoretical studies of hydrodynamic lubrication in slider bearings have been carried out by many investigators 1,2) in the past due to ease in its mathematical modeling. In some early works only Reynolds equation was solved in order to compute the bearing performance parameters.…”
Section: Overviewmentioning
confidence: 99%
“…Allaire and Flack [11] have provided a detailed discussion on the design and application of various oil journal bearing con®gura-tions. A state-of-art study on recent analyses and designs of journal and thrust bearings has been reported by Tanaka [12]. The above-mentioned work relates to plain cylindrical oil journal bearings.…”
mentioning
confidence: 99%
“…In 1997, Tanaka [36] published a review of analyses and designs of thick ®lm bearings that included a section concerned with automotive engine bearings. Tanaka noted that relatively little work had been published concerning transient (i.e.…”
Section: Theoretical Bearing Modelsmentioning
confidence: 99%